Dopaminergic circuits underlying associative aversive learning - Zafiri, Daphne; Duvarci, Sevil (Frontiers in Behavioral Neuroscience, 2022)
Associative aversive learning enables animals to predict and avoid threats and thus is critical for survival and adaptive behavior. Anxiety disorders are characterized with deficits in normal aversive learning mechanisms and hence understanding the neural circuits underlying aversive learning and memory has high clinical relevance. Recent studies have revealed the dopamine system as one of the key modulators of aversive learning. In this review, we highlight recent advances that provide insights into how distinct dopaminergic circuits contribute to aversive learning and memory.